Analisis Yuridis Penjatuhan Pidana Terhadap Pejabat Negara Yang Melakukan Tindak Pidana Korupsi Terkait Penyalahgunaan Kewenangan : Studi Putusan Pengadilan Negeri Medan Nomor : 12/Pid.Sus-Tpk/2018/PN.Mdn - Rizki Syahbana Amin Harahap; Syafruddin Kalo; Madiasa Ablisar; Sutiarnoto Sutiarnoto (Universitas Sumatera Utara, 2019)
Abstract. Corruption is a tremendous crime (extra ordinary crime). Corruption crimes propagated into the regency of coal in the projects of 2016 and the year 2017, in this case the awarding of gifts to the coal regent and Head of the Department of Public Works and spatial Arrangement (PUPR), has received a prize Or the promise of coal regent of Rp. 8,055,000,000.00 and head of the PUPR service amount of Rp. 80,000,000.00. Analyzed the state of incrimination and relieve the state of criminal proceedings against the government officials and the consideration of the law of the state court against the officials who conduct corruption in Court verdict Number: 12/Pid. Sus-TPK/2018/PN.Mdn. Misuse of authority made by state officials is governed by LAW No. 30 of 2014 on government administration, misuse of authority occurs because of non-negligence or omission. The incriminating circumstances and the alleviating circumstances in the ruling on which the tribunal judges do must conform to the characteristics: 1). The form of nature, atmosphere or situation, 2) the formulation is found outside of its own action, 3) describes The seriousness of the act or the degree of the state officials who commit a corruption criminal. Court ruling No. 12/Pid. Sus-TPK/2018/Pn. MDN is deemed to have not been precise in conducting criminal proceedings, as legal considerations at the coal regent and the head of the PUPR office have a state of incrimination, deeds Defendant proved legitimately and assured the elements of 12 letters (a) UU No. 20 Year 2011 about the amendment of LAW No. 31 of 1999 on corruption criminal eradication, element of article 55 paragraph (1) of the criminal CODE, and the element of article 65 paragraph (1) of the criminal CODE in accordance with what By the public prosecutor. Keywords: abuse of authority, corruption crimetative analysis method.